Multiple Pigmented Bowen’s Disease: A Diagnostic and Therapeutic Dilemma - Pratik Gahalaut; Madhur Kant Rastogi; Nitin Mishra; Sandhya Chauhan (Case Reports in Oncological Medicine)
Bowens' disease (BD) is a precancerous condition of skin and/or mucosa with a predilection towards sun-exposed areas. Extensive literature research failed to reveal any case of multiple pigmented BD in type V Fitzpatrick skin. Multiple BD is a therapeutic challenge with a tendency to recur. Here we present an otherwise healthy Indian male having multiple pigmented lesions of BD on sun-protected sites of the body mimicking malignant melanoma. These lesions were refractory to treatment with different modalities. This paper is an attempt to review the available literature regarding the pigmented variant of multiple BD. Rationale for a therapeutic trial of UVB therapy for multiple arsenic induced BD is also discussed.